THE PLANNING PROCESSES IMPROVEMENT OF THE STRUCTURES DISSOLUTION WITH TAKING INTO ACCOUNT THE OPERATIONAL DATA OF THE CONTROL FREIGHT AUTOMATED SYSTEMS - Bardas, O. O. (Science and Transport Progress, 2008)
The specified model of definition of the order of trains processing on the switching stations considering operative data of automatic management systems of freight transportation is developed.